(3QSGdI aj GdWHs - (3GdMcje HbQGWs
(3ChdgG (B:s
(3bGd HbQGW (B: (3CYde Cfg ef CcKQ ef TQH GdeGA aj ZPGFI , aSOJ eYOJg, hVYa Yf gVe GdWYGe s
(3BNQgG (B:s
(3hJQcg jhekG hdjdI , aEPG UM cTag hjOgfg ceG JbOe , hjeO bdjdG bdjdG ceG PcQfG , hdGHO Cf jeO GdYVh HgPG GdJOHjQ , hgh UMjM eLQH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B107 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3LGeYI HZOGO (B(453) s
Keywords: (3GdWHs